Short- and long-term impact of remarkable economic events on the growth causes of China–Germany trade in agri-food products - Guo, Zhichao; Feng, Yuanhua; Tan, Xiangyong (Economic Modelling)

A blueprint for event-driven business activity management - Janiesch, Christian; Matzner, Martin; Müller, Oliver (Lecture Notes in Computer Science)
Keywords: Reference architecture; business activity management; business process analytics; business process management; complex event processing

Leaving the Beaten Tracks in Creative Work – A Design Theory for Systems that Support Convergent and Divergent Thinking - Müller-Wienbergen, Felix; Müller, Oliver; Seidel, Stefan; Becker, Jörg (Journal of the Association for Information Systems)
Keywords: Creativity; Creativity Support Systems; convergent thinking; design theory; divergent thinking

Walk your talk: an experimental investigation of the relationship between word of mouth and communicators’ loyalty - Garnefeld, Ina; Helm, Sabrina; Eggert, Andreas (Journal of Service Research)

Industrial services, product innovations, and firm profitability: A multiple-group latent growth curve analysis - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Muenkhoff, Eva (Industrial Marketing Management)

Exploring the Impact of Sales Technology on Salesperson Performance: A Task-Base d Approach - Eggert, Andreas; Serdaroglu, Murat (Journal of Marketing Theory and Practice)

Who follows the crowd—Groups or individuals? - Fahr, René; Irlenbusch, Bernd (Journal of Economic Behavior & Organization)

Job design and job satisfaction—empirical evidence for Germany? - Fahr, René (management revue)

When the early bird catches the worm: The impact of training in retail - Hinerasky, Christiane; Fahr, Rene

Key Account Management - Ivens, Björn; Eggert, Andreas (Handbuch Vertriebsmanagement)

HRM and the use of personnel services: an empirical analysis of German firms - Alewell, Dorothea; Hauff, Sven; Weiland, Katrin; Thommes, Kirsten (International journal of manpower)

HR outsourcing and service quality: theoretical framework and empirical evidence - Braun, Irene; Pull, Kerstin; Alewell, Dorothea; Störmer, Susi; Thommes, Kirsten (Personnel Review)

Workshop 16 Individuelle Förderung. Konzepte und Erfahrungen zur Berufsorientierung im Übergang - Beutner, Marc; Kremer, H.-Hugo; Zoyke, A. (bwp@ Spezial 5 - Hochschultage Berufliche Bildung 2011)

Fachtagung 19 (bwp@ Spezial 5 - Hochschultage Berufliche Bildung 2011)

Lernfeldansatz - 15 Jahre danach - Kremer, H.-Hugo; Tramm, T.; Tenberg, R. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Room temperature spin relaxation length in spin light-emitting diodes - Soldat, Henning; Li, Mingyuan; Gerhardt, Nils C.; Hofmann, Martin R.; Ludwig, Arne; Ebbing, Astrid; Reuter, Dirk; Wieck, Andreas D.; Stromberg, Frank; Keune, Werner; Wende, Heiko (Applied Physics Letters)

Surface acoustic wave controlled carrier injection into self-assembled quantum dots and quantum posts - Krenner, Hubert J.; Völk, Stefan; Schülein, Florian J. R.; Knall, Florian; Wixforth, Achim; Reuter, Dirk; Wieck, Andreas D.; Kim, Hyochul; Truong, Tuan A.; Petroff, Pierre M. (physica status solidi (c))

Modellbasiertes Testen: Hype oder Realität? - Weißleder, Stephan; Güldali, Baris; Mlynarski, Michael; Törsel, Arne-Michael; Faragó, David; Prester, Florian; Winter, Mario (OBJEKTspektrum)
Manuelle Testerstellung verursacht hohe Kosten. Im Vergleich dazu bietet modellbasiertes Testen große Vorteile hinsichtlich Testautomatisierung, früher Fehlerfindung, Erhöhung der Testabdeckung, effizienten Testentwurfs und besserer Rückverfolgbarkeit. Die Einführung des modellbasierten Testens ist jedoch mit Investitionen verbunden, für die die Rendite häufig unklar erscheint. Dabei finden sich in der Literatur bereits etliche Erfahrungsberichte zur erfolgreichen Einführung von modellbasiertem Testen in unterschiedlichen Anwendungsdomänen. In diesem Artikel präsentieren wir einen Überblick über einige dieser Erfahrungsberichte.

TORC: test plan optimization by requirements clustering - Güldali, Baris; Funke, Holger; Sauer, Stefan; Engels, Gregor (Software Quality Journal)
Acceptance testing is a time-consuming task for complex software systems that have to fulfill a large number of requirements. To reduce this effort, we have developed a widely automated method for deriving test plans from requirements that are expressed in natural language. It consists of three stages: annotation, clustering, and test plan specification. The general idea is to exploit redundancies and implicit relationships in requirements specifications. Multi-viewpoint techniques based on RM-ODP (Reference Model for Open Distributed Processing) are employed for specifying the requirements. We then use linguistic analysis techniques, requirements clustering algorithms, and pattern-based requirements collection to reduce the total effort of testing against the requirements specification. In particular, we use linguistic analysis for extracting and annotating the actor, process and object of a requirements statement. During clustering, a similarity function is computed as a measure for the overlap of requirements. In the test plan specification stage, our approach provides capabilities for semi-automatically deriving test plans and acceptance criteria from the clustered informal textual requirements. Two patterns are applied to compute a suitable order of test activities. The generated test plans consist of a sequence of test steps and asserts that are executed or checked in the given order. We also present the supporting prototype tool TORC, which is available open source. For the evaluation of the approach, we have conducted a case study in the field of acceptance testing of a national electronic identification system. In summary, we report on lessons learned how linguistic analysis and clustering techniques can help testers in understanding the relations between requirements and for improving test planning.

Using rule overriding to improve reusability and understandability of Dynamic Meta Modeling specifications - Soltenborn, Christian; Engels, Gregor (Journal of Visual Languages & Computing)
Dynamic Meta Modeling (DMM) is a visual semantics specification technique targeted at languages based on a metamodel. A DMM specification consists of a runtime metamodel and operational rules which describe how instances of the runtime metamodel change over time. A known deficiency of the DMM approach is that it does not support the refinement of a DMM specification, e.g., in the case of defining the semantics for a refined and extended domain-specific language (DSL). Up to now, DMM specifications could only be reused by adding or removing DMM rules. In this paper, we enhance DMM such that DMM rules can override other DMM rules, similar to a method being overridden in a subclass, and we show how rule overriding can be realized with the graph transformation tool GROOVE. We argue that rule overriding does not only have positive impact on reusability, but also improves the intuitive understandability of DMM semantics specifications.